Drying of pisang salai by using oven - Wan Lokman Wan Haron (2011)
Pisang salai is one of the traditional foods since ancient times. Banana drying steps using the clothes line to expose to the sun is one way to make banana durable and not easily damaged when stored. Therefore, this thesis aimsto examine one of drying techniques to a produce pisang salai by using heat oven different temperatures. Experiment on drying of pisang salai was conducted in the laboratory of the Faculty of Agro and Natural Resources, University of Malaysia Kelantan. This experiment was aimed at studying the differences between sun drying and oven used for drying technique to produce pisang salai. By oven drying was found to be much faster and cleaner. In addition, sun drying technique is not suitable for the production of pisang salai in large quantities and has slower rate in drying besides pisang salai easily exposed to the risk of contamination by dust, insects and other dirt and unstable weather factor. In the study, it was found that the temperature 60° C was suitable for pisang salai drying. In addition, this experiment can also be used as a first step to commercialize products based on bananas in the local community. With this study, efforts to develop small industry in particular among the villagers will be able to help the economy than to give them returns. In addition, this study can be seen more on the application of technology in the production of banana-based food products. It is very important as a way to avoid losses if the overflow of bananas at a time that causes bananas cannot be sold whole and eventually rot and damage.